Protective effects of propofol against hydrogen peroxide-induced oxidative stress in human kidney proximal tubular cells - Yu Mi Lee; Jin Woo Shin; Eun Ho Lee; Youngjin Moon; Young Joo Seo; Ji Yeon Kim; Joung Uk Kim (Korean Journal of Anesthesiology, 2012)
BackgroundWe investigated the protective effects of propofol in the HK-2 cell line of human kidney proximal tubular cells against hydrogen peroxide (H2O2)-induced oxidative stress.MethodsAfter pretreatment with different concentrations of propofol (0 µM, 10 µM, 25 µM and 50 µM) for 30 minutes, HK-2 cells were exposed to 8 mM H2O2 for 4 hours. Cell death was assessed by measuring the percentage of lactate dehydrogenase (LDH) release and by counting viable cells. The nature of cell death was assessed by doubles-taining cells with fluorescein isothiocyanate-labeled Annexin V and propidium iodide, and then analyzing the cells using flow cytometry.ResultsAfter exposure to 8 mM H2O2 for 4 hours, the percentage of LDH release was 45.1 ± 4.2% and the number of viable HK-2 cells was 5.2 ± 6.0%. Pretreatment with propofol suppressed H2O2-induced LDH release in a concentration-dependent manner, reducing the percentage of LDH release to 38.1 ± 5.6%, 33.5 ± 6.3%, and 26.2 ± 3.8% of the controls at 10 µM, 25 µM and 50 µM propofol, respectively. Numbers of viable cells increased following propofol pretreatment, with 11.4 ± 10.9%, 19.5 ± 16.1%, and 32.4 ± 23.3% cell survival rates after pretreatment with 10 µM, 25 µM and 50 µM propofol, respectively. Analyses of flow cytometry showed that the propofol pretreatment decreased the percentage of necrotic and late apoptotic cells.ConclusionsPropofol protects HK-2 human kidney proximal tubular cells against H2O2-induced oxidative stress.